DIVERSE AND TISSUE-SPECIFIC MITOCHONDRIAL RESPIRATORY RESPONSE IN A MOUSE MODEL OF SEPSIS-INDUCED MULTIPLE ORGAN FAILURE. Issue 4 (April 2016) - Karlsson, Michael; Hara, Naomi; Morata, Saori; Sjövall, Fredrik; Kilbaugh, Todd; Hansson, Magnus J.; Uchino, Hiroyoki; Elmér, Eskil
Abstract : ABSTRACT: Mitochondrial function is thought to play a role in sepsis-induced multiple organ failure. However, the temporal and organ-specific alterations in mitochondrial function have yet to be fully elucidated. Many studies show reduced phosphorylating capacity, while others have indicated that mitochondrial respiration is enhanced. The objective of this study was to evaluate the temporal dynamics of brain and liver mitochondrial function in a mouse model of sepsis. Sepsis was induced by cecal ligation and puncture. Controls were sham operated. Using high-resolution respirometry, brain and liver homogenates from 31 C57BL/6 mice were analyzed at either 6 or 24 h. Reactive oxygen species (ROS) production was simultaneously measured in brain samples using fluorometry. Septic brain tissue exhibited an early increased uncoupling of respiration. Temporal changes between the two time points were diminutive and no difference in ROS production was detected. Liver homogenate from the septic mice displayed a significant increase in the respiratory control ratio at 6 h. In the 24-h group, the rate of maximal oxidative phosphorylation, as well as LEAK respiration, was significantly increased compared with controls and the resultant respiratory control ratio was also significantly increased. Maximal protonophore-induced respiratory (uncoupled) capacity was similar between the two treatment groups. The present study suggests a diverse and tissue-specific mitochondrial respiratory response to sepsis. The brain displayed an early impaired mitochondrial respiratory efficiency. In the liver the primary finding was a substantial activation of the maximal phosphorylating capacity.